2017
DOI: 10.5114/kitp.2017.70530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, management and mortality in diabetic and non-diabetic patients with heart failure – observations from the COMMIT-HF registry

Abstract: IntroductionDiabetes mellitus (DM) and heart failure (HF) are two common diseases that often co-exist.AimTo explore clinical characteristics, management strategies and rates of 3-year mortality among diabetic and non-diabetic patients hospitalised in a highly specialized interventional cardiology centre.Material and methodsWe used data from COMMIT-HF (COnteMporary Modalities In Treatment of Heart Failure), which is a single-centre, observational, prospective registry of patients with symptomatic chronic systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…In this study, the overall mortality rate in the entire subpopulation of women with heart failure and diabetes was more than five times greater than for women with heart failure without diabetes. These findings are supported by previous studies that have shown a two-fold to a three-fold increased risk of mortality due to heart failure in the diabetic population [1,2,21,22,33].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the overall mortality rate in the entire subpopulation of women with heart failure and diabetes was more than five times greater than for women with heart failure without diabetes. These findings are supported by previous studies that have shown a two-fold to a three-fold increased risk of mortality due to heart failure in the diabetic population [1,2,21,22,33].…”
Section: Discussionsupporting
confidence: 90%
“…The findings from the present study support recently published findings on the impact of diabetes mellitus on clinical outcomes in patients with heart failure due to ischemic and non-ischemic cardiac disease [2,3,[31][32][33][34]. In 2016, a study from the Swedish Heart Failure Registry (SwedeHF) analyzed patient data from 2003 to 2011 and showed that heart failure was a severe complication of type 2 diabetes mellitus [34].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is also the most common cause of hospitalisation after the age of 65 years and the cause of the deaths of 60,000 Poles a year [1][2][3]. Heart failure is most often caused by coronary heart disease, previous myocardial infarction, hypertension, heart valve defects, alcoholism, obesity, and diabetes [4][5][6]. Among patients hospitalised with HF the prevalence of diabetes mellitus is 42.6% and remains associated with increased frequency of death in this population [4].…”
Section: Heart Failure As a Health And Social Problemmentioning
confidence: 99%